The Uptake and Impact of a Label for Peer-Reviewed Books - Vandewalle, Eline; Guns, Raf; Engels, Tim C. E. (Frontiers in Research Metrics and Analytics, 2022)
This article presents an analysis of the uptake of the GPRC label (Guaranteed Peer Reviewed Content label) since its introduction in 2010 until 2019. GPRC is a label for books that have been peer reviewed introduced by the Flemish publishers association. The GPRC label allows locally published scholarly books to be included in the regional database for the Social Sciences and Humanities which is used in the Flemish performance-based research funding system. Ten years after the start of the GPRC label, this is the first systematic analysis of the uptake of the label. We use a mix of qualitative and quantitative methods. Our two main data sources are the Flemish regional database for the Social Sciences and Humanities, which currently includes 2,580 GPRC-labeled publications, and three interviews with experts on the GPRC label. Firstly, we study the importance of the label in the Flemish performance-based research funding system. Secondly, we analyse the label in terms of its possible effect on multilingualism and the local or international orientation of publications. Thirdly, we analyse to what extent the label has been used by the different disciplines. Lastly, we discuss the potential implications of the label for the peer review process among book publishers. We find that the GPRC label is of limited importance to the Flemish performance-based research funding system. However, we also conclude that the label has a specific use for locally oriented book publications and in particular for the discipline Law. Furthermore, by requiring publishers to adhere to a formalized peer review procedure, the label affects the peer review practices of local publishers because not all book publishers were using a formal system of peer review before the introduction of the label and even at those publishers who already practiced peer review, the label may have required the publishers to make these procedures more uniform.